2023
DOI: 10.3390/diagnostics13010164
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricle and Radiotherapy: More Questions than Answers

Abstract: The injury of the left ventricle (LV) during anticancer therapy has long been recognized, and guidelines recommend a specific set of parameters for determination of LV impairment. The influence of anticancer therapy on the right ventricle (RV) has been insufficiently investigated, and there are only a few studies that have considered the effect of radiotherapy on RV remodeling. On the other hand, large number of patients with different types of cancers located in the chest are treated with radiotherapy, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…On the other hand, Christiansen et al found a prevalence of RVSD of 28.2% [8]. The underlying reason for this noticeable high prevalence may lie in the more intensive treatment received by the recruited survivors: the cumulative anthracycline dose was 150 (40-485) mg/m 2 , and 24% of them were exposed to radiotherapy, which appears to exert a particularly cardiotoxic effect on the RV due to its anterior anatomical position [25]. In addition, the lower limits of normal RV function were based on the distribution of the control group values, resulting in more lenient criteria for RV impairment.…”
Section: Prevalence Of Right Ventricle Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Christiansen et al found a prevalence of RVSD of 28.2% [8]. The underlying reason for this noticeable high prevalence may lie in the more intensive treatment received by the recruited survivors: the cumulative anthracycline dose was 150 (40-485) mg/m 2 , and 24% of them were exposed to radiotherapy, which appears to exert a particularly cardiotoxic effect on the RV due to its anterior anatomical position [25]. In addition, the lower limits of normal RV function were based on the distribution of the control group values, resulting in more lenient criteria for RV impairment.…”
Section: Prevalence Of Right Ventricle Dysfunctionmentioning
confidence: 99%
“…The median age at diagnosis was 4 (3-8) years, and the median time elapsed from diagnosis to recruitment was 18 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) years. All the survivors were exposed to anthracyclines, but only three (3.3%) received radiotherapy.…”
Section: Cardiotoxic Treatment Exposurementioning
confidence: 99%